Effect of data size on tooth numbering performance via artificial intelligence using panoramic radiographs - AKGÜN, GAZİ (My University, 2023)
Objective: This study aims to investigate the effect of number of data on model performance, for the detection of tooth numbering problem on dental panoramic radiographs, with the help of image processing and deep learning algorithms. Study Design: The data set consists of 3000 anonymous dental panoramic X-rays of adult individuals. Panoramic X-rays were labeled on the basis of 32 classes in line with the FDI tooth numbering system. In order to examine the relationship between the number of data used in image processing algorithms and model performance, four different datasets which include 1000, 1500, 2000 and 2500 panoramic X-rays, were used. The training of the models was carried out with the YOLOv4 algorithm and trained models were tested on a fixed test dataset with 500 data and compared based on F1 score, mAP, sensitivity, precision and recall metrics. Results: The performance of the model increased as the number of data used during the training of the model increased. Therefore, the last model trained with 2500 data showed the highest success among all the trained models. Conclusion: Dataset size is important for dental enumeration, and large samples should be considered as more reliable.
Keywords: Tıp; Dahili Tıp Bilimleri; Nükleer Tıp; Diş Hekimliği; Sağlık Bilimleri; Medicine; Internal Medicine Sciences; Nuclear medicine; Dentistry; Health Sciences; Klinik Tıp (MED); Klinik Tıp; DİŞ HEKİMLİĞİ, ORAL CERRAHİ VE TIP; RADYOLOJİ, NÜKLEER TIP ve MEDİKAL GÖRÜNTÜLEME; Clinical Medicine (MED); CLINICAL MEDICINE; DENTISTRY, ORAL SURGERY & MEDICINE; RADIOLOGY, NUCLEAR MEDICINE & MEDICAL IMAGING; Diş Hekimliği (çeşitli); Radyoloji, Nükleer Tıp ve Görüntüleme; Dentistry (miscellaneous); Radiology, Nuclear Medicine and Imaging; Artificial intelligence; Health technologies; Image processing; Panoramic x-ray; Tooth numbering